Shaming and employer social insurance compliance behaviour in Shanghai - Nyland, Chris; Hartel, Charmine; Thomson, Stanley Bruce; Zhu, Cherrie Jiuhua (My University, 2012)
Social security regimes must be underpinned by enforcement mechanisms designed to compel employers to fulfil their contribution requirements. In this paper we extend debate on China’s social security system by discussing whether the inclusion of re-integrative shaming in the repertoire of mechanisms the state utilises to enforce employer compliance is likely to prove effective. Drawing on audited data provided by the Shanghai Bureau of Labour and Social Security and on interviews with employers and Bureau staff we argue that though shaming has the potential to become an important social security enforcement mechanism in China, optimism that this will occur in the near future is not justified.
Keywords: compliance; employer; China; shaming; social security